CGAS‐STING pathway: post‐translational modifications and functions in sterile inflammatory diseases. (1st August 2021) - Hong, Ze; Ma, Tianchi; Liu, Xing; Wang, Chen
Abstract : Cytoplasmic microbial and host aberrant DNAs act as danger signals and trigger host immune responses. Upon recognition, the cytosolic DNA sensor cyclic GMP–AMP synthase (cGAS) catalyzes the production of a second messenger 2′3′‐cGAMP, which activates endoplasmic reticulum (ER)‐associated stimulator of interferon (IFN) genes (STING) and ultimately leads to the induction of type I IFNs and inflammatory genes that collectively initiate host immune defense against microbial invasion. Inappropriate activation or suppression of this signaling pathway has been implicated in the development of some autoimmune diseases, sterile inflammation, and cancers. In this review, we describe how the activity of cGAS and STING is regulated by host post‐translational modifications and summarize the recent advances of cell‐specific cGAS‐STING activation and its association in sterile inflammatory diseases. We also discuss key outstanding questions in the field, including how our knowledge of cGAS‐STING pathway could be translated into clinical applications. Abstract : We discuss here how multiple post‐translational modifications on cyclic guanosine monophosphate–adenosine monophosphate synthase (cGAS) and stimulator of interferon gene (STING) allow the initiation of rapid responses against pathogenic DNAs and a timely control of invading pathogens, which plays a critical role in the maintenance of cellular and organismal homeostasis under physiological conditions. Conversely, aberrant activation of cGAS‐STING signaling in specific immune and nonimmune cells promotes the progression of multiple autoimmune and inflammatory diseases.